REPRESENTATION OF THE “FAMILY” CONCEPT IN PHRASEOLOGICAL UNITS - Nurmuhammedov, Yusuf (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
Nowadays, in world linguistics, special attention is paid to clarifying the issue of national-cultural specificity of universal concepts on the example of units of different language levels. In particular, in Uzbek linguistics, different views are being formed about the linguocognitive features of the concept, which is widely used to reveal the interrelationship of language, human and cultural phenomena. However, in the Uzbek scientific literature, there is no research devoted to the conceptualization of the concept of "Family" with the help of thematic and statistical analysis on the example of phraseological units. In this article, firstly, it is determined that the integrative approach allows to study the concepts from the linguistic, cognitive, cultural and sociological point of view. Secondly, according to the phraseo-semantic field method, the concept of "family" is composed of core and peripheral parts, and with the help of statistical analysis, it is revealed that the concept is also consist of the core and the near, middle and outermost peripheries. Research shows that conceptualization is a mental way of reflecting reality in the human mind. It combines subjective and traditional meanings accepted by the linguistic community. Through the prototypical categorization of the concept, it is concluded that language and cultural identity are transparently manifested. The obtained results serve to acquire a deeper understanding of foreign languages and cultures
Keywords: concept; category; notion; approach; integrative; semantic interpretation; association; periphery; core